The implementation of formative assessment in B. Ed. TESL program in higher education / Aisyah Nazamud-Din - Nazamud-Din, Aisyah (2015)
This study is a mixed-method study on the implementation of formative assessment practices in higher education. The purpose of the study is to investigate the practices of formative assessment in B.Ed TESL program in terms of 1) assignment practices, 2) quantity and timing of feedback practices 3) quality of feedback practices and 4) utilization of feedback practices. Moreover, this study investigated the challenges faced by the students in formative assessment and strategies to improve formative assessment in the program. The respondents of the descriptive survey were 105 undergraduates in B.Ed TESL program. Four students and four lecturers were selected to participate in the interview sessions in this study. The result showed that the practices of assignment, quantity and timing of feedback, quality of feedback and the utilization of feedback in the program were at the moderate level. There was a significant difference in the utilization of feedback between genders of students. The relationships between the four dimensions were found to be from low to moderate strength. Furthermore, the challenges in employing formative assessment were relating to personal attitudes, language skills, learning skills, lecturers and peers. Suggestions to improve the practices included giving constructive feedback, enhancing the utilization of feedback and improving the conduct of assignments. It is hoped that the study will contribute to the improvement of formative assessment practices in the program and the policies to implement it. This study indicated that formative assessment practices could benefit the students, the lecturers and the stakeholders in the field.